Physical Basis for Creating Energy and Resource-Saving Rheo-Technology in Oil Production - Emin A. Panakhov; Tulparkhan Sh. Salavatov (Energies, 2009)
In a previous paper we presented the results of our investigations on the application of externally imposed temperature fields for the improvement of the non-Newtonian properties of raw oil in the well and also on the possible use of electric and magnetic fields in the water flooding process of the oil layer. In this article, some additional results are presented with regards to the application of external pressure fields to the same purpose, with the goal of increasing the well output and improve the efficiency of gaslift wells and oil pipelines. The possibility of regulating the gas-liquid system saturation pressure is discussed as well, to expand the opportunity of varying the well operating regime.